IMPLANT SUPRACRESTAL COMPLEX CONDITIONING THROUGH THE “X TECHNIQUE” TO ACHIEVE AN ENHANCED MUCO-CERVICAL IMPRINT. CASE REPORTS - Miselli, Alberto (2025)
In dentistry, predictable and successful implant treatments demand a comprehensive understanding of the biological mechanisms related to hard and soft tissue changes. The objective of this case reports is to describe in two patients, the conditioning of the implant supracrestal complex (ISC) through the "X Technique", aiming to achieve an enhanced muco-cervical imprint of an individualized emergence profile conformer, reproducible for the emergence profile of the final prosthetic restoration, safeguarding ISC health with the use of active oxygen/lactoferrin gel (blue®m) and ISC stability with the proposed surgical-prosthetic protocol. The technique involves oblique subperiosteal incisions in an "X" pattern with meticulous tissue manipulation to modify peri-implant mucosa phenotype, enhance the buccal contour, and stimulate papilla formation without resorting to additional mucosal grafts. Clinical significance: The technique described offers a promising approach in obtaining a predictable and reproducible muco-cervical imprint or footprint of the prosthetic emergence profile framed within the ISC. Offering to achieve key parameters such as supracrestal tissue height (STH), ISC integrity, muco-cervical imprint stability and implant mucosa thickness (MT) displaying stability. This underscores the effectiveness of the technique in ensuring the sustained health and aesthetics of peri-implant tissues. Further longterm studies are needed to quantify the benefits of this technique in increasing keratinized tissue width (KTW) and MT effectively.